How does renewable energy consumption affect economic growth? Evidence from the European Union countries - Davidson Natalia; Maksimova Elizaveta; Mariev Oleg (SHS Web of Conferences, 2021)
Research background: Fossil fuels are used at such a high rate that they are currently being depleted. Moreover, they are associated with a greenhouse effect leading to global warming. Meanwhile, green energy is naturally replenished and fosters sustainable development (Nelson and Starcher, 2015). However, the empirical evidence of the impact of green energy on economic growth is controversial (Adewuyi and Awodumi, 2017; Chen et al., 2020; Destek and Aslan, 2017; Zafar et al., 2018). Purpose of the article: This paper analyses the impact of renewable energy consumption on economic growth in the European Union (EU) countries. This is important in line with the goals of EU to shift towards green energy during the coming years (Directive (EU) 2018/2001). Methods: We use data of the World Bank and Our World in Data over 1990 to 2015 for 28 EU countries. We estimate the impact of renewable energy consumption on the countries’ gross domestic product. The control variables are labor force, research and development, and foreign direct investment. We apply the pooled mean group, mean group, the dynamic fixed effect estimators (Pesaran, 1997; Pesaran et al., 1999), and generalized method of moments (Arellano & Bond, 1991). Findings & Value added: Results show that the renewable energy consumption positively affects economic growth of the EU countries. We contribute by shedding light on the possibility to develop renewable energy, while achieving economic growth. The results have important implications for economic policy.